1980
DOI: 10.1029/gl007i011p00974
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of stratospheric aerosols to small amounts of ammonia in the laboratory environment

Abstract: Trace ammonia in laboratory air reacts easily with sulfuric acid aerosol samples to form crystalline ammonium sulfate. Using argon atmospheres, however, we have succeeded in protecting sampling surfaces from ammonia contamination. We find that atmospheric aerosols treated in this way contain only sulfuric acid. After an hour exposed to laboratory air, these same samples convert to ammonium sulfate. We are continuing to collect aerosol particles, using argon control, to determine if the absence of crystalline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Stratospheric sulfate particles are formed in an ammonia-poor environment. Hayes et al (1980) found, by using an electron diffraction technique, that stratospheric aerosol particles contained no ammonium sulfate when aerosol samples were protected by argon from ammonia contamination. Considering very small ammonia concentration in the stratosphere and special protection mech- Lion technique, that stratospheric aerosol particles contained no ammonium sulfate when aerosol samples were protected by argon from ammonia contamination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stratospheric sulfate particles are formed in an ammonia-poor environment. Hayes et al (1980) found, by using an electron diffraction technique, that stratospheric aerosol particles contained no ammonium sulfate when aerosol samples were protected by argon from ammonia contamination. Considering very small ammonia concentration in the stratosphere and special protection mech- Lion technique, that stratospheric aerosol particles contained no ammonium sulfate when aerosol samples were protected by argon from ammonia contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Considering very small ammonia concentration in the stratosphere and special protection mech- Lion technique, that stratospheric aerosol particles contained no ammonium sulfate when aerosol samples were protected by argon from ammonia contamination. Considering very small ammonia concentration in the stratosphere and special protection mechanism found by Hayes et al (1980), Russell and Hamill (1984) concluded that all the stratospheric particles contain primarily sulfuric acid. Our result is consistent with these workers' conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of ammonium salts particles in the stratosphere has been doubted by Hayes et al (1980). They pointed out that sulfuric acid droplets were converted rapidly into ammonium sulfate particles by absorbing ambient ammonia in laboratory-room air before identification.…”
Section: Introductionmentioning
confidence: 99%
“…Recently McMurry et al (1983) also reported high values of *=0.40 to 0.18 for particles of 0.058 to 0.1 am diameter. According to Hayes et al (1980), sulfuric acid droplets collected on an electronmicroscopic grid are converted entirely into ammonium sulfate particles within one hour by exposure to laboratory-room air. On the basis of Hayes' experiments, 10-2 was taken tentatively as the value of * for the entire conversion from a sulfuric acid droplet into an ammonium sulfate particle.…”
Section: Introductionmentioning
confidence: 99%